2003
DOI: 10.3184/030823403103173291
|View full text |Cite
|
Sign up to set email alerts
|

The biotransformation of the Diterpenoid, Rosenonolactone by Mucor Plumbeus

Abstract: The biotransformation of rosenonolactone by the fungus, Mucor plumbeus involves hydroxylation at C-2α C-6β C-12α and epoxidation of the Δ15-alkene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…2). Our results were consistent with the data reported in references (Dockerill et al, 1978;Hanson et al, 2003) except for the two positions at CH 2 -6 and CH 2 -11 (Table 2).…”
Section: Identification Of Compoundssupporting
confidence: 95%
See 3 more Smart Citations
“…2). Our results were consistent with the data reported in references (Dockerill et al, 1978;Hanson et al, 2003) except for the two positions at CH 2 -6 and CH 2 -11 (Table 2).…”
Section: Identification Of Compoundssupporting
confidence: 95%
“…Here 1 H and 13 C NMR data were assigned based on 2D-NMR experiments ( Table 2). The NMR data of compound 1 were very similar to those of desoxyrosenonolactone (4) and 2Į-hydroxyrosenonolactone (Hanson et al, 2003), but after careful analysis we found four obvious dissimilarities between compounds 1 and 4. Thus, we think the OH group position is different in the two compounds.…”
Section: Identification Of Compoundsmentioning
confidence: 57%
See 2 more Smart Citations
“…In the course of our continuing efforts to find new and bioactive natural products from higher fungi, a strain of T. versicolor was subjected to chemical investigation. Four new spiroaxane sesquiterpenes tramspiroins A-D (1-4) and one new rosenonolactone 15,16-acetonide (5) [12] were isolated, along with the known drimane sesquiterpenes isodrimenediol (6) and funatrol D (7) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%